Development of a patient-reported outcome (PRO) measure to assess patient perceptions of simplicity and complexity of treatment for type 2 diabetes - Katie D. Stewart; Louis S. Matza; Hiren Patel; Kristina S. Boye (SpringerOpen, 2023)
Abstract Introduction Treatments for type 2 diabetes vary widely in their complexity. The simplicity or complexity of a treatment regimen may have an impact on patient preference, treatment adherence, and health outcomes. The purpose of this qualitative study was to develop two draft patient-reported outcome instruments focusing on patients' experience with simplicity and complexity of treatment for type 2 diabetes. Methods The instruments were developed in a series of steps: gather information to support development of a concept elicitation interview guide (literature review and expert interviews), concept elicitation interviews with patients (N = 30), cognitive interviews with patients (N = 20), and a translatability assessment. Results In concept elicitation interviews, patients with type 2 diabetes reported a range of treatment attributes that influence their perceptions of treatment simplicity and complexity, such as injection devices, medication preparation, dose timing, dose frequency, ease of taking the correct dose, flexibility of dose schedule, remembering to take medication, and food requirements. Two draft questionnaires were developed based on the literature review, expert interviews, and concept elicitation interviews with patients. Revisions were made to these draft instruments based on qualitative interviews with patients and translatability assessment. Discussion The qualitative research conducted in this study supports the content validity of two newly developed instruments, the Simplicity of Diabetes Treatment Questionnaire (Sim-Q) and the Simplicity of Diabetes Treatment Questionnaire-Comparison (Sim-Q-Comp), designed to assess the simplicity and complexity of diabetes treatment from the patient's perspective.